ATMOSFIR TOKO SEBAGAI STRATEGI MEMPENGARUHI EMOSI BELANJA KONSUMEN (Studi Empiris pada Toko Buku Retail di Kota Malang) - Fuad, Muhammad; Hadiati, Sri (JURNAL MANAJEMEN DAN AKUNTANSI, 2014)
Store atmosphere is designed to stimulate a positive emotional response of consumers in effort to increase their spending activity. However, some businesses still tend to ignore the atmosphere as a marketing tool. This study aimed to analyze the store atmosphere as a marketing strategy that affects consumerâs spending emotions, as well as to identify the variable of the atmosphere that predominantly affects the emotions. Berman and Evansâ approach (2001), which identified the store exterior, general interior, store layout, and interior display as the variables of atmosphere, was used as the research baseframe. The results stated the four variables of store atmosphere were significantly influence the spending emotions of consumer, both simultaneously and partially. Furthermore, this study also identifies the characteristics of consumers who frequently shop at retail bookstores in Malang City. Kata kunci : Earning Response Coefficient (ERC,) leverage, size, voluntary disclousureKeywords: Store atmosphere, store exterior, general interior, store layout, interior display, spending emotion